Diabetes and abnormal glucose regulation in the adult population of Burkina Faso: prevalence and predictors - Tieba Millogo; Brice W. Bicaba; Joseph Kouesyandé Soubeiga; Estelle Dabiré; Isaie Médah; Séni Kouanda (BMC, 2018)
Abstract Background The prevalence of diabetes mellitus (DM) is reportedly growing fast in sub-Saharan Africa. There is however a scarcity of epidemiologic data on DM in Burkina Faso. We carried out a secondary analysis of the first survey conducted in Burkina Faso on a nationally representative sample following the World Health Organization (WHO) Stepwise approach to risk factors Surveillance (STEPS) for non-communicable diseases (NCDs) with the aims of identifying the prevalence of NCDs and the prevalence of common risk factors for NCDs. We report here on the prevalence of diabetes and overall abnormal glucose regulation (AGR) and their associated risk factors. Methods In the primary study 4800 individuals were randomly sampled using a stratified multistage clusters sampling process. We used fasting capillary whole blood glucose level to define three glucose regulation statuses using WHO's cut-off levels: normal, diabetes and overall abnormal glucose regulation (impaired fasting glucose and diabetes). Appropriate statistical techniques for the analysis of survey data were used to identify the factors associated with diabetes and abnormal glucose regulation fitting a logistic regression model. Analyses were carried out using Stata Version 14 software. Results The prevalence of DM and AGR were respectively 5.8% (95% CI: 5-6.7) and 9% (95% CI: 8-10.1). Significant risk factors for DM include age (OR = 1.9; P = 0.009 for the age group of 55-64), obesity (OR: 2.6; P = 0.001), former smoke (OR:2; P = 0.03), second-hand smoke (OR = 1.7; P = 0.006) and total cholesterol level (OR: 2.1; P = 0.024). The same predictors were also found significantly associated with AGR. In addition, having an history family diabetes was protective against AGR (OR = 0.5; P = 0.032). Conclusion Diabetes is no longer a rare disease in the adult active population of Burkina Faso. Its burden is significant in both rural and urban areas. Health policies that promote healthy life style are needed to give precedence to the prevention in a context of an under-resourced country.